Software configuration management handbook - Leon, Alexis (Artech House, 2015)
This new resource is a complete guide to implementing, operating, and maintaining a successful SCM system for software development. Project managers, system designers, and software developers are presented with not only the basics of SCM, but also the different phases in the software development lifecycle and how SCM plays a role in each phase.